PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS AUGMENTED REALITY - Anggrainy Wulandari; Samijo Samijo; Darsono Darsono (UNEJ e-Proceeding, 2022)
This research is motivated by the rapidly technological development that can be used in purpose of making a learning media more interesting and concise. One of the learning media development is Augmented Reality. Augmented Reality become popular right now. By using Augmented Reality as an alternative learning media, it is hoped that a learning activity can be more interesting for students. The problem of this research is whether Augmented Reality-based mathematics learning media on flat-sided geometry with sub-materials of surface area and volume of flat-sided geometry attracts students? This research is using Research and Development (R&D) type. The result of this research is that the augmented reality-based mathematics learning media, named GEORANS, is very decent to be used in the learning process in schools, in accordance with the results of validation by five validators with successive percentages of 92.5 percent, 92.5 percent, 87.5 percent, 97.5 percent, 82.5 percent. As well as the average results of the questionnaire conducted by class VIII MTS NU Plosoharjo students obtained a percentage of 84.17 percent. The conclusion is that the learning media GEORANS is categorized as fascinating learning media to use at school. Keywords: Learning Media, Augmented Reality, Flat-sided Geometry